Emotional intelligence and communication competence: An Empirical Investigation of Secondary Education School Principals - Χριστοφορίδου, Ευτέρπη; Πλατσίδου, Μαρία (Education Sciences, 2020)
The aim of this study was to test the hypothesis that secondary education school Principals with higher emotional intelligence have better communication skills. In the first phase of the survey, 11 Principals were tested with the Mayer-Salovery-Caruso Emotional Intelligent Test (Mayer, Caruso & Salovey, 2000). Of these, 2 Principals with the highest and 3 Principals with the lowest performance were selected to be tested for their communication skills with a semi-structured interview. The results showed that Principals with higher actual emotional intelligence have better communication skills than those with lower emotional intelligence. The former Principals, according to their answers, can communicate their message clearly and transfer their vision in their school comunity.